Farmers as knowledge brokers: Analysing three cases from Vietnam's Mekong Delta - Quy-Hanh Nguyen; Hans-Dieter Evers (University of Bonn, Center for Development Research (ZEF), 2011)
The paper explores the novel dimensions of agrarian change and of an agricultural knowledge-creation culture in Vietnam's Mekong Delta by examining cases of farmers engaged in knowledge brokering. Farmers empowered with knowledge, and through intensive engagement in networks and communities of practice, are taking an increasingly more important role in diffusing and (re)producing knowledge via brokering services. This research investigates the development path, brokerage undertakings and knowledge networking practiced by farmers, who act as knowledge brokers. In addition, it analyses the stories and knowledge flow networks of three selected cases. The analysis is contextualised in the diffusion of the VACB farming system, designed to make small-scale rural farming more sustainable through integrated horticulture (V), pisciculture (A), animal husbandry (C) and biogas installation (B). The findings suggest an appreciation of farmer-constructed learning structures in managing knowledge diffusion, and an integration of informal knowledge flows into the common agricultural/rural development goals of responsible organisations and the sector. An extended framework of knowledge diffusion management is also proposed. The data used in this analysis were collected during a one-year field research project in the Mekong Delta within the period April 2010 - 11.
Keywords: 330; knowledge brokering farmers; knowledge diffusion management; VACB farming system; narratives; network analysis; Mekong Delta